Development of a Novel Nonlinear Dynamic Cavitation Model and Its Numerical Validations (Advances in Applied Mathematics and Mechanics, 2024)
Aiming at modeling the cavitation bubble cluster, we propose a novel nonlinear dynamic cavitation model (NDCM) considering the second derivative term inRayleigh-Plesset equation through strict mathematical derivation. There are two improvements of the new model: i) the empirical coefficients are eliminated by introduction of the nonuniform potential functions of $ψ_v$ and $ψ_c$ for growth and collapse processes respectively, and ii) only two model parameters are required, which both baseon physical quantities – the Blake critical radius $R_b$ and the average maximum growthradius $R_m.$ The corresponding cavitation solver was developed by using OpenFOAMin which we implemented the modified momentum interpolation (MMI) method toensure that the calculated results are independent of time step size. Three validationcases, namely numerical bubble cluster collapse, ultrasonic horn experiment, and hydrodynamic cavitation around slender body are employed. The results indicate that $ψ_v$ and $ψ_c$ can reveal the nonlinear characteristics for cavity accurately, and $R_b$ and $R_m$ can reflect the relevance between cavitation model and actual physical quantities.Moreover, it is discussed the potentiality of NDCM that is generally applied on thecavitating flow possessing with dispersed bubbly cloud.